DIPLODON CF. COLHUAPIENSIS (BIVALVIA, HYRIIDAE) IN THE SANTA CRUZ FORMATION (EARLY–MIDDLE MIOCENE) AT THE RÍO SANTA CRUZ, PATAGONIA, ARGENTINA. STRATIGRAPHIC AND PALEOENVIRONMENTAL CONSIDERATIONS - Leandro Martín Pérez; José Ignacio Cuitiño; Augusto Nicolás Varela; Nahuel Antú Muñoz (Publicación Electrónica de la Asociación Paleontológica Argentina, 2019)
The Santa Cruz Formation (Early–Middle Miocene) is one of the most widespread sedimentary units of the Argentine Patagonia. This unit contains an abundant and taxonomically diverse fossil vertebrate fauna, especially in mammals. Thus, the paleoecological and paleoenvironmental information derives mainly from the analysis of the vertebrate assemblages, as well as from the ichnological and paleobotanical evidence. The record of freshwater bivalves assigned to the species Diplodon cf. colhuapiensis Ihering, 1903 from the Santa Cruz Formation, collected in the locality of Barrancas Blancas (Estancia Santa Lucía), at Río Santa Cruz, allows us to infer the particular paleoenvironmental conditions setting during the deposition of the bearing levels. Considering this record, we propose that Diplodon, which was originally assigned to the “Sehuenense stage” (piso sehuenense of F. Ameghino), could have come from the Early–Middle Miocene of the Santa Cruz Formation. In this sense, the specimens referred to Diplodon cf. colhuapiensis suggest the existence of an established community of Hyriidae mollusks at the upper-middle levels of the Santa Cruz Formation. The presence of freshwater bivalves suggests that the depositional environment of this unit included the existence of water courses. The identification of the genus in the Santa Cruz Formation validates its presence in the Early Miocene and extends its southern distribution to the latitude of Río Santa Cruz (~ 50o S).